Clear tracks or missed connections? A qualitative study exploring how interest-holder perceptions of purpose shape the implementation and experience of the six-month review for stroke survivors - Rich Holmes; Suzanne Ackerley; Dawn Goodwin; Louise A. Connell (PLoS ONE, 2025)
Introduction The six-month review (6MR) for stroke survivors is recommended in clinical guidelines. However, the purpose of the review lacks clarity and has been implemented in variable ways. This study aims to better understand the purpose of the 6MR by comparing and contrasting the perspectives of different interest-holders, and to identify what impact this might have on the functioning of services. Method This paper reports a qualitative analysis drawn from a multiple case study project. Participants were recruited from three interest-holder groups: Service Providers (staff members), Service Influencers (managers, commissioners and regional leaders), and Service Users (stroke survivors and their carers). Data were collected from semi-structured interviews, clinical observations, and documentary evidence. Interest-holder groups were analysed separately using reflexive thematic analysis. Themes were then compared across interest-holder groups. Results Thirty-six participants were recruited across three interest-holder groups: Service Providers (n = 8), Service Influencers (n = 6), and Service Users (n = 22). Seven themes were identified: two each for Service Providers and Service Influencers, and three for Service Users. Service providers emphasised a desire to deliver person-centred care but were often constrained by systemic pressures. Service influencers saw the review primarily as a mechanism for population-level data collection and service planning, while also acting as a safety net to capture unmet or evolving needs. Service users typically viewed the review as a routine check-up rather than a pivotal moment in the pathway. For some, it marked the end of formal support while others valued the sense of reassurance and validation it provided. Conclusion Interest-holders have differing views on the purpose of the 6MR, with tensions emerging between system-level priorities and person-centred care. Greater clarity on the function of the 6MR may help reduce unwarranted variation in its implementation and ensure it delivers meaningful value to all involved.